The Effectiveness of Online Learning Using YouTube Streaming Media on Learning Kitab kuning Fathul Qorib at Pondok Pesantren Raudhotul Muttaqin Talun Sukodadi Lamongan - Lukmanul Hakim; Siti Latihfatus Sun'iyah (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2024)
This research is based on the effectiveness of learning kitab kuning Fathul Qorib using YouTube streaming media at the Raudhotul Muttaqin Islamic Boarding School Talun Sukodadi Lamongan, which was basically carried out during the covid 19 period and until now YouTube streaming media is still used in learning kitab kuning kitab kuning because it is felt that this media is very helpful in learning. The purpose of this writing is (1) to find out the application and effectiveness of online learning using YouTube streaming media on learning the kitab kuning of fathul qorib at the Raudotul Muttaqin Islamic Boarding School Talun Sukodadi Lamongan. This research uses a quantitative approach using an experimental research design. Data collection techniques in this study used observation, interviews, tests and documentation techniques. It is said to be experimental because in this study researchers used two groups, namely experimental and control groups to see the difference between groups taught using YouTube streaming media and not. The results of this study, it can be seen that the use of YouTube streaming media can help students to better understand the material from the recitation of the kitab kuning kitab kuning even though they are not in the boarding school. The results also show that there is a significant effect of using YouTube streaming media on the learning outcomes of students and alumni, this is based on the t-Independent Test through the SPSS type 23 application with the t test results found a t value of 5,150 with a sig (2-tailed) of 0.000. Because the sig value <0.05, it can be concluded that there is a difference between the learning outcomes of the control class students and the experimental class after the test.